Novel Biogenic Synthesis of Pd/TiO@BC as an electrocatalytic and possible energy storage materials - Khasim, Syed; Dastager, Syed G.; Alahmdi, Mohammed Issa; Hamdalla, Taymour A.; Panneerselvam, Chellasamy; Makandar, Mohammad Basha (Ceramics International, 2023)
The standard approach towards synthesizing nanomaterials exercising chemical or physical techniques generally costs more and necessitates using toxic chemicals, which negatively affect the environment. For the first time, an investigation of a basic green synthesis approach for Phyto fabrication of Pd/TiO@BC nanocomposite via biomass of rice husk (Oryza sativa L) is conducted to sustain the green chemistry for synthesis of less toxic chemicals. XRD analysis revealed that the structure of Phyto synthesized Pd/TiO@BC is crystalline, while UV, FTIR, SEM and EDX analyses marked the victorious nanocomposite biosynthesis. We have investigated the electrocatalytic and biomedical applications of the novel nanocomposite Pd/TiO@BC at different environmental conditions. Testing the potential electrochemical properties of Pd/TiO@BC to eliminate the Congo red (CR) dye from wastewater marked its high removal efficiency, which attained 90% owing to the higher electron efficiency. Its sensitivity for CR was also examined, and acceptable degradation activity was observed. These Pd/TiO@BC proved to be beneficial in various fields, including electrochemistry, catalysis sensors, wastewater treatment, and nano-devices, and in the transformation of hazardous particles into less harmful substances. Its great potential for use as a supercapacitor is promised by its feature, including durability and compact stability. Significant guidelines could be extracted from the results, which are helpful in material size, synthesis, selection, and configuration design for various energy storage gadgets. The synthesis of high performance and economical materials through green chemistry is a novel approach towards effective energy storage and alteration procedure operation.
Keywords: Electro catalytic; Energy storage; Oryza sativa L biochar; Pd; PdNPs and TiONPs; TiO@BC